Multiyear aerosol observations with dual-wavelength Raman lidar in the framework of EARLINET - Mattis, I.; Ansmann, A.; Mueller, D.; Wandinger, U.; Althausen, D. (Journal of Geophysical Research: Atmospheres, 2004)
For the first time, a Raman lidar operating simultaneously in the ultraviolet (UV) and in the visible wavelength range was employed to measure vertical profiles of volume extinction coefficients of particles at 355 and 532 nm, the respective Angstromngstrom exponent, and the 355-nm and 532-nm extinction-to-backscatter ratio ( lidar ratio) on a routine basis for several years. The long-term observations were performed at Leipzig (52degreesN, 12degreesE), Germany, in the framework of the European Aerosol Research Lidar Network (EARLINET) project from May 2000 to March 2003. The lidar data were acquired under nighttime conditions. The main findings describe the mean optical properties of central European haze ( anthropogenic particles) and can be summarized as follows. The 3-year mean, planetary boundary layer (PBL) extinction coefficients were 191 Mm(-1) at 355 nm and 94 Mm(-1) at 532 nm. The respective mean Angstromngstrom exponent (for the 355-532-nm wavelength range) was 1.4 in the upper PBL (above 1000 m). The PBL stretched, on average, to heights of 1300 m ( winter) and 2350 m (summer). PBL mean particle optical depths were 0.38 (355 nm, +/-0.23 standard deviation) and 0.18 (532 nm, +/-0.11 standard deviation). Free tropospheric particles contributed 2% (clean free troposphere) to 88% ( major Saharan dust events) to the tropospheric optical depth. The average was 17% (355 nm) and 22% (532 nm) in 2000-2003. Angstromngstrom exponents in the free troposphere of about one reflect the dominant influence of Saharan dust and aged smoke on the optical properties in this height range. Three-year mean lidar ratios of 58 sr (355 nm) and 53 sr ( 532 nm) were found in the upper part of the PBL. Free tropospheric lidar ratios were on average 52 sr ( 355 nm) and 53 sr ( 532 nm). From combined observations with the Aerosol Robotic Network (AERONET) Sun photometer and the EARLINET lidar, extinction-to-backscatter ratios at 1064 nm were estimated to be, on average, 45 sr. A comparison with optical measurements made at the ...